Hubungan Ketiadaan Orang Tua Terhadap Pilihan Anak Hidup Di Jalanan (Studi Deskriptif Anak Jalanan di Kelurahan Padang Bulan, Medan) - Khalil Gibran Daulay (Departemen Sosiologi Universitas Sumatera Utara, 2012)
ABSTRACT Generally, street children in Medan City are come from a lower economic family. This economic condition is the main reason why these childrens go to work in a street in order to help their family. This study had been conducted at Simpang Pos which is a well known location where street children doing their activities. Type of this study is descriptive qualitative, with 8 (eight) interviewees. Data had been collected by study of literature, internet data sources as well as field study: observation, semi-open questionnaires, in-depth interviews and documentation. Study result indicate that street childrens in Medan come from poor families, in order to support needs of their families they have to work on the street. Type of work they do is a work in informal sector such as street singing, cleaning cars etc. Key Word: Street Children, Absence Of Parents.